The fundamentals of small group communication - Myers, Scott A. (Sage Publications, 2008)
Overview: The Fundamentals of Small Group Communication provides readers with the fundamentals they need to become functional and productive members of any small group. Readers are introduced to the fundamental issues faced by all small groups (such as socialization, development, ethics, diversity) and the procedures utilized by effective small groups (for example, task accomplishment, decision making, climate). With a focus on the individual group member, this textbook encourages readers to reflect on how their communication behaviors (e.g., communication traits, verbal and nonverbal communication, listening style) and practices (e.g., their leadership style, their conflict management style) contribute to their current small group experiences.